Kreativitas Mahasiswa KKN UNRI Meriahkan 1 Muharram dan 17 Agustus Serta Penyuluhan Mencegah Stunting - Hasnah Faizah; Riski Alfalah; Andi Firdaus Yohaini; Selin Rosalina; Ega Anggraini; Nabilatuzzahwa Nabilatuzzahwa; Govin Taj Mukhti; Ratih Kumala Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
Pulau Jambu village, located in Kampar Regency, Riau, Indonesia, has an area of 60.7 km2 and a population of around 3,254 people, with the majority adhering to Islam. This village is divided into four hamlets: Sungai Betung, Kampung Panjang, Kampung Baru, and Pulau Jambu. This article describes the four main pillars that form the essence of Indonesian people's lives in Pulau Jambu Village: the